Genotypic, phenotypic and environmental correlations in 81 genotypes of tomato tree (Cyphomandra betacea Cav. Sendt.) - Duarte A., David Esteban; Lagos B., Tulio Cesar; Lagos S., Liz Katherine (Revista de Ciencias Agrícolas, 2013)
This research was carried out to evaluate different components of fruit quality, to estimate phenotypic, genetic and environmental correlations in tree tomato (Cyphomandra betacea), considering 14 variables related to fruit size and quality, and to establish direct and indirect effects of traits related to fruit weight. Data of 81 hybrids with two replications were taken account of, in the municipality of Pasto, Colombia. The results indicated that genotypic correlations were higher than phenotypic and environmental ones. Fruit weight (FW) showed the highest genetic correlations (rG 0.60), with more pulp and seed weight (rG 0 0.90) and equatorial diameter (rG = 0.84). Path analysis based on genotypic correlations showed that internal thickness (EI) was the variable that had the greatest direct effect(1.63) demonstrating that a selection on the basis of fruit weight will result in an increase of the internal thickness. Taking into account the phenotypic correlations, it was established by analysis that the direct effects of equatorial diameter(DE) and polar diameter (DP), (0.30) and (0.26) respectively are the major contributors to fruit weight (PF).